Pituitary dysfunction and its association with quality of life in traumatic brain injury. (April 2016) - Izzo, Giulia; Tirelli, Assunta; Angrisani, Elisabetta; Cannaviello, Giovanni; Cannaviello, Lucio; Puzziello, Alessandro; Vatrella, Alessandro; Vitale, Mario
Abstract: Background: Traumatic brain injury (TBI) is a major cause of death and disability and may cause transient or persistent, isolated or multiple hypopituitarism in a variable percentage of cases. Objectives: The primary aim of this study was to determine the incidence of isolated and multiple anterior pituitary hormone deficiency in subjects with TBI in a single institution. The secondary aim was to determine a correlation between pituitary deficiency and quality of life (QOL) after TBI. Methods: Thirty-five patients, aged between 18 and 63 years, were evaluated 6months to 5 years after TBI. We evaluated the QOL by SF-12 ® questionnaire and measured serum basal GH, IGF1, LH, FSH, testosterone (in males), 17-β-estradiol (in women), PRL, fT4 and TSH. In patients with low IGF1, a GHRH + Arginine test was performed. Results: Single or multiple pituitary failure was found in 13 patients (37%). Low testosterone was found in 7 males, low FSH and/or LH in 4, low IGF1 in 7 patients. Hypogonadotropic hypogonadism and GH insufficiency assessed by GHRH + Arginine test were found respectively in 3 and 2 patients. One patient displayed a concomitant GH insufficiency and low TSH level. Twenty six patients showed a reduction in QOL. A correlations between altered QOL and hormonal deficiency was not observed. Conclusions: Isolated or multiple hypopituitarism resulting from TBI are frequent. Alterations in QOL and pituitary function resulting from TBI are not associated.